1978
DOI: 10.1111/1523-1747.ep12557535
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of the Role of Pityrosporum orbiculare in Pityriasis Versicolor and the Significance of Extracellular Lipase

Abstract: Pityrosporum orbiculare is an obligate lipophilic yeast in vitro, which suggests it possesses an extracellular lipase crucial for nutrition. If present in vivo, the enzyme would enable the yeast to utilize skin surface lipids, which may therfore play an important role in the pathogenesis of pityriasis versicolor. Cultured P. orbiculare and biopsy material from patients with pityriasis versicolor were investigated for the presence of lipase by electron microscope histochemistry. At sites of lipase activity, fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Among these organisms, P. ovale and P. orbiculare have been considered as resident microorganisms of the normal human skin and also as pathogenic agents of tinea versicolor (4,8,17,18), dermatitis seborrheica (17), comedones (21), and folliculitis (10).…”
Section: Discussionmentioning
confidence: 99%
“…Among these organisms, P. ovale and P. orbiculare have been considered as resident microorganisms of the normal human skin and also as pathogenic agents of tinea versicolor (4,8,17,18), dermatitis seborrheica (17), comedones (21), and folliculitis (10).…”
Section: Discussionmentioning
confidence: 99%
“…They have lipolytic activity both in vitro (301,459) and in vivo (85,272), indicating the production of a lipase. The lipase is located in the cell wall and/or membrane sites in the cytoplasm (85,349).…”
Section: Structure Physiology and Biochemistrymentioning
confidence: 99%
“…They have lipolytic activity both in vitro (301,459) and in vivo (85,272), indicating the production of a lipase. The lipase is located in the cell wall and/or membrane sites in the cytoplasm (85,349). Ran et al (349) found that the pH optimum was 5.0 and that lipase production was greatest during the logarithmic phase of growth, perhaps demonstrating its importance in the hydrolysis of lipids for cell growth.…”
Section: Structure Physiology and Biochemistrymentioning
confidence: 99%
“…Besides their important role in biotechnology, these reactions have been discussed as potential virulence factors in pathogenic bacteria and fungi. Other studies have demonstrated the ability of M. furfur to release fatty acids from different lipids (Catterall et al, 1978;Hammer & Riley, 2000;Mancianti et al, 2001). Ran et al (1993) did not detect lipases in the supernatant, but determined that the main lipolytic activity was in the insoluble fraction of cell extracts.…”
Section: Introductionmentioning
confidence: 95%